Synthesis of Macrocycles Derived from Substituted Triazines. (5th December 2018) - Yepremyan, Akop; Mehmood, Arshad; Asgari, Parham; Janesko, Benjamin G.; Simanek, Eric E.
Abstract: A triazine ring derivatized with morpholine, an N ‐alkyl‐ N′ ‐BOC‐hydrazine (alkyl=isopropyl or benzyl) and the diethylacetal of glycinylpropionaldehyde undergoes spontaneous dimerization in good yields upon acid‐catalyzed deprotection. The resulting 24‐member macrocycles can be characterized by NMR spectroscopy, mass spectrometry, and single crystal X‐ray diffraction. In the solid state, both homodimers adopt a taco‐like conformation. Although each shows π–π stacking between the triazine rings, different patterns of hydrogen bonds emerge. The crystal structure of the isopropyl dimer shows that it includes two molecules of trifluoracetic acid per macrocycle. The trifluoroacetate anion charge balances the protonated triazines, which engage in bifurcated hydrogen bonds with the carbonyl acceptor of the distant glycine. This carbonyl also forms a hydrogen bond with the NH of the proximate glycine. The crystal structure of the benzyl derivative does not include trifluoracetic acid. Instead, two hydrogen bonds form, each between a glycine NH and the lone pair of the C=N nitrogen of the hydrazine group. In the solid state, both molecules present the alkyl side chains and morpholine groups in close proximity. A heterodimer is accessible in approximately statistical yields—along with both homodimers—by mixing the two protected monomers prior to subjecting them to deprotection. Abstract : Bicycle made from two : Condensation of a small molecule bearing an aldehyde and hydrazine group leads to macrocycles, specifically dimers, in excellent yields. The design rests on a substituted [1, 3, 5]‐triazine that affords multiple sites for the incorporation of structural diversity.